2019
DOI: 10.1021/acsearthspacechem.9b00220
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Oxide Catalyzed Hydrolysis of Polyphosphates

Abstract: Polyphosphate (polyP) is a group of important phosphorus (P) species that plays critical roles in the marine P cycle and potentially mediates phosphorus (P) burial in sediments. Revealing the transformation of polyP is important for understanding the P cycle in aquatic environments. This study systematically investigated the hydrolysis of polyP with different chain lengths by four representative types of manganese (Mn) oxides (α-MnO 2 , β-MnO 2 , δ-MnO 2 , and birnessite) under varied solution conditions. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…S4), consistent with the slow disproportionation reported for Mn(III)-PP at circum-neutral pH (Qian et al, 2019). The minor decrease of Mn(III)-PP after 12 h is possibly related to Mn oxides catalyzing PP hydrolysis (Wan et al, 2019).…”
Section: The Oxidation Of As(iii) By Birnessite With/without Chelating Agentssupporting
confidence: 85%
“…S4), consistent with the slow disproportionation reported for Mn(III)-PP at circum-neutral pH (Qian et al, 2019). The minor decrease of Mn(III)-PP after 12 h is possibly related to Mn oxides catalyzing PP hydrolysis (Wan et al, 2019).…”
Section: The Oxidation Of As(iii) By Birnessite With/without Chelating Agentssupporting
confidence: 85%
“…Previous studies show that orthophosphate and myo -inositol hexakisphosphate adsorption on Fe and Al (oxyhydr)­oxides generally occurs through the formation of bidentate binuclear surface complexes via surface ligand exchange. ,,, Polyphosphates differ from these molecules in that they have a chain of middle P groups that can also interact with mineral surfaces in addition to the terminal phosphate groups and in that polyphosphates with different chain lengths possess different molecular elasticities. Our recent research revealed that polyphosphates can be readily hydrolyzed on Al and manganese (Mn) oxide surfaces via the gradual cleavage of the terminal P groups, suggesting the tendency of polyphosphate terminal P groups to form bidentate binuclear complexes with surface Mn/Al atoms. ,, According to QCM results, the adsorption amount (surface density of P unit) is similar for polyphosphates with different chain lengths. This suggests that polyphosphate molecules may adopt a lay-down configuration on mineral surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent research revealed that polyphosphates can be readily hydrolyzed on Al and manganese (Mn) oxide surfaces via the gradual cleavage of the terminal P groups, suggesting the tendency of polyphosphate terminal P groups to form bidentate binuclear complexes with surface Mn/Al atoms. 17,20,54 According to QCM results, the adsorption amount (surface density of P unit) is similar for polyphosphates with different chain lengths. This suggests that polyphosphate molecules may adopt a lay-down configuration on mineral surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Future studies should consider supporting an effort to characterize the range of inorganic polyP chain lengths in marine systems. Due to the roles of polyP in geologic P sequestration (Diaz et al ., 2008 ; Huang et al ., 2018 ; Wan et al ., 2019a , 2019b , 2021 ) and microbial nutritional physiology, a greater understanding of the molecules that make up the polyP component of particulate and dissolved marine P pools may have larger implications for marine P cycling, DOM biogeochemistry and ecosystem functioning.…”
Section: Discussionmentioning
confidence: 99%